FLEXIBLE WORK RELATIONSHIP MODEL IN THE MAXIM DIGITAL TRANSPORTATION INDUSTRY IN GORONTALO - Butudoka, Lasmi H.; Husain, Alifya Nurfadilah; Sabbu, Aldi Bregi; Moobiato, Sri Anggriani; Poiyo, Indriyani; Habi, Novita E.; Harold, Rudi (Academic Solution Publisher, 2025)
This study aims to analyze the flexible work relationship model in the Maxim digital transportation industry in Gorontalo, focusing on working-hour flexibility, income, algorithmic control, and social protection for driver-partners. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The findings indicate that work flexibility provides advantages for drivers in adjusting their work to personal needs; however, it also creates income uncertainty due to dependence on the number of orders and platform algorithms. Most drivers are not registered in social security schemes, exposing them to social and economic risks. Algorithmic control limits drivers’ autonomy despite their freedom to determine working hours. This study recommends the integration of social security coverage, greater algorithmic transparency, digital literacy enhancement, and collaboration among government, companies, and drivers to create a fair and sustainable work ecosystem.